Dietary supplementation of Citrus bioflavonoids improves lactation performance in buffaloes during hot weather by regulating antioxidant capacity, immune function, and rumen microbes - Li, Yinghui; Yao, Hanxing; Li, Chenglong; Li, Mengwei; Chen, Fengming; Huang, Xingguo; Yang, Chengjian (Frontiers in Veterinary Science, 2025)
Citrus bioflavonoids (CB) are well recognized for their antioxidant, anti-inflammatory, and digestion-promoting properties. This study aimed to evaluate the effects of dietary CB supplementation on apparent nutrient digestibility, lactation performance, blood biochemical/immunological parameters, and the ruminal microbial community of dairy buffaloes during hot weather. A 35-day trial was conducted using 20 Mediterranean dairy buffaloes, which were randomly assigned to two groups: a control group (CON) fed a basal diet, and a CB-supplemented group (CB) fed the basal diet plus 20 g/d of CB. The results showed that compared with the CON group, CB supplementation significantly reduced (p < 0.05) the respiratory rate, and increased (p< 0.05) the apparent digestibility of acid detergent fiber in buffaloes. Regarding lactation performance, CB supplementation significantly elevated (p< 0.05) milk yield, 4% fat corrected milk, and the percentage of milk protein, lactose, and solids-not-fat; it also increased the concentrations of polyunsaturated fatty acids and conjugated linoleic acids in milk while decreasing (p < 0.05) the concentration of saturated fatty acids. For blood parameters, the CB group exhibited significantly higher (p < 0.05) blood catalase activity, immunoglobulin M concentration, and heat shock protein 70 concentration, as well as significantly lower (p < 0.05) concentrations of the pro-inflammatory cytokines tumor necrosis factor-α, interleukin (IL)-1β, and IL-6. In terms of ruminal function, CB supplementation significantly increased (p < 0.05) ruminal microbial crude protein concentration. There was a tendency toward higher (0.05 < p < 0.10) microbial α-diversity indices (Chao 1, Ace, and Shannon) in the CB group, accompanied by the enrichment of several bacterial genera within the family Lachnospiraceae and other saccharolytic taxa, and the suppression of the genus Segatella. In conclusion, dietary supplementation with 20 g/d CB enhances the lactation performance of heat-stressed dairy buffaloes by improving the ruminal microenvironment and host health status.